Effectivitas of Murottal Therapy on Primiparas Pregnant Mother in the Third Trimester - Indrayani, Triana; Andriani, Yeni (GLOBAL HEALTH SCIENCE GROUP, 2023)
Pregnancy is a physiological process, and as the pregnancy progresses, the mother experiences physical and mental changes that can cause pregnancy problems. One of the most common problems for pregnant women, especially those in their third trimester, is insomnia. One way that can be done to overcome the problems and complaints of insomnia among pregnant women is to use murotal therapy. The aim of this research is: To determine the effect of Murotal therapy on the sleep quality of Primiparous Pregnant Women in Trimester 3. Methodology: This type of research is Quasi Experimental with a 1 group pre and post test design. The population in this study were all pregnant women in the third trimester with a gestational age of 28 weeks - 38 weeks and had complaints of sleep disorders with a sample size of 16 people. The sampling technique is purposive sampling. Data were analyzed univariately and bivariately with the Wilcoxon t test. Data was collected using an observation sheet consisting of a pretest sheet and a posttest sheet. Results: The results of the Wilcoxon hypothesis test showed that there was a change in the sleep quality of primiparous pregnant women in the third trimester with a p value of 0.001 (p > 0.05). Conclusion: Murotal therapy is effective in treating insomnia in third trimester primiparous pregnant women.